2006
DOI: 10.1021/ja060251t
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Alanine Tripeptide with Antiparallel and Parallel β-Sheet Structures in Relation to the Analysis of Mixed β-Sheet Structures in Samia cynthia ricini Silk Protein Fiber Using Solid-State NMR Spectroscopy

Abstract: The structural analysis of natural protein fibers with mixed parallel and antiparallel beta-sheet structures by solid-state NMR is reported. To obtain NMR parameters that can characterize these beta-sheet structures, (13)C solid-state NMR experiments were performed on two alanine tripeptide samples: one with 100% parallel beta-sheet structure and the other with 100% antiparallel beta-sheet structure. All (13)C resonances of the tripeptides could be assigned by a comparison of the methyl (13)C resonances of Ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(106 citation statements)
references
References 30 publications
10
96
0
Order By: Relevance
“…A complementary approach exists which consists in the synthesis and investigation of bio-inspired simplified peptides that provide invaluable information in the understanding of their natural counterparts (69,71,78,139). The study of specific properties found in natural fibers isolated in synthetic polypeptides should lead us to a better understanding of their functioning and the production of improved synthetic materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complementary approach exists which consists in the synthesis and investigation of bio-inspired simplified peptides that provide invaluable information in the understanding of their natural counterparts (69,71,78,139). The study of specific properties found in natural fibers isolated in synthetic polypeptides should lead us to a better understanding of their functioning and the production of improved synthetic materials.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the 13 C-13 C dipolar coupling can be reintroduced by coherent schemes such as radio-frequency driven recoupling (RFDR) (68). Performed on fully 13 C-labeled alanine tripeptides, Asakura et al (69) used 2D 13 C- 13 C RFDR MAS spectra to assign 13 C resonances in parallel and antiparallel b-sheet structures. This method, applicable to natural fibers, revealed subtle differences in chemical shifts and interpeptides contacts at long mixing times.…”
Section: Correlation Experiments Under Masmentioning
confidence: 99%
“…15 The shape of the Ala Cb peak is known to be related not only to the conformation of the peptide but also to the intermolecular arrangement of the peptides. [16][17][18] Regarding the Ala Cb signal in the spectrum for AE12, the broad peak at 18.2 p.p.m. was assigned to the random coil peptides, and the other peaks at lower field were all derived from the b-sheet structures.…”
Section: Resultsmentioning
confidence: 99%
“…NMR signals arising from the major amino acid residues were well resolved and easily assigned to the peaks of Gly, Ala, Ser, Tyr and the amorphous region (including random coil and α-helix), 18 as shown in Fig. 3.…”
Section: Atomic Level Analysismentioning
confidence: 93%
“…The chemical shifts centered at 172 ppm was assigned to the peak of Gly on the crystalline region. 18,19 That peak intensity of the 5-day aged sample increased, while with the increasing degrading times, it gradually decreased. As shown in Fig.…”
Section: Atomic Level Analysismentioning
confidence: 96%